2023
DOI: 10.1128/aac.00356-23
|View full text |Cite
|
Sign up to set email alerts
|

The Plasmodium Lactate/H + Transporter PfFNT Is Essential and Druggable In Vivo

Abstract: Malaria parasites in the blood stage express a single transmembrane transport protein for the release of the glycolytic end product l -lactate/H + from the cell. This transporter is a member of the strictly microbial formate-nitrite transporter (FNT) family and a novel putative drug target.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Conditional knockout demonstrated the essentiality of the pf f nt gene during the blood stage, whereas phenotypic defects were not observed during the sexual development of the parasite. 122 An inhibitor of Pf FNT in this later study was found to possess high potency in P. berghei-and P. falciparum-infected mice, with their in vivo activity profiles being comparable to that of artesunate. Taken together, these data confirmed the validity and druggability of Pf FNT as an antimalarial target.…”
Section: Plasmodium Ispd (2-c-methyl-d-erythritol 4-phosphate Cytidyl...mentioning
confidence: 65%
“…Conditional knockout demonstrated the essentiality of the pf f nt gene during the blood stage, whereas phenotypic defects were not observed during the sexual development of the parasite. 122 An inhibitor of Pf FNT in this later study was found to possess high potency in P. berghei-and P. falciparum-infected mice, with their in vivo activity profiles being comparable to that of artesunate. Taken together, these data confirmed the validity and druggability of Pf FNT as an antimalarial target.…”
Section: Plasmodium Ispd (2-c-methyl-d-erythritol 4-phosphate Cytidyl...mentioning
confidence: 65%